Perceptions of Grammar-Focused Mobile Applications Among HSC Learners Across Bangladesh: An Exploratory Mixed-Methods Study - Tanvir Mostafa (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study explored the perceptions of Higher Secondary Certificate (HSC) learners in Bangladesh toward grammar-focused mobile applications and their role in grammar practice, motivation, and writing confidence. Methods – An exploratory mixed-methods design was used. Questionnaire data were collected from 50 HSC students representing 16 colleges in 16 districts across all 8 administrative divisions of Bangladesh, and 10 students participated in follow-up semi-structured interviews. Quantitative responses were summarized using descriptive statistics, while interview data were analyzed thematically. Findings – Students generally viewed grammar apps positively. Most respondents agreed that the apps made grammar learning engaging, easy to use, and motivating. Interactive exercises (86%), user interface (80%), feedback mechanisms (76%), and gamification (70%) were the most valued features. Interviews showed that students appreciated convenience, immediate correction, and short game-like practice; however, they also reported short explanations, limited contextual examples, internet dependence, storage problems, and possible overreliance. Research implications – As the sample was purposive and based on learner perceptions, the findings should be interpreted as exploratory rather than statistically generalizable. The results suggest that grammar apps can supplement classroom teaching when guided by teachers, but they should not replace formal instruction. Originality – The study contributes national exploratory evidence from HSC learners across all divisions of Bangladesh and highlights both pedagogical value and equity concerns in mobile-assisted grammar learning.